BASIC PRINCIPLES OF HUMAN RESOURCES MANAGEMENT IN ISLAMIC ECONOMY (International Conference on Social and Islamic Studies, 2022)
Humans were created by Allah SWT in order to live their lives on earth as khalifatullah fil ardh, this shows that humans cannot live haphazardly, they should follow the rules set by those who created them, but the events are different, if you look at the damage that is happening everywhere On this earth, humans prey on each other, wars occur everywhere, massive exploitation which sometimes does not take into account the damage that may occur to nature and the environment, crimes in society are sometimes difficult to detect because of selfishness, greed and the desire to dominate. However, there is also a lot of goodness happening on this earth, namely those who recognize and follow the guidance given by religious teachings, especially those who are aware that their creation is to be beings who must properly manage this earth, preventing damage that may or may not cause damage to nature and its environment. To be able to find out, the author tries to describe it by conducting library research and looking for other supporting documents to then see a solution to this condition. It turns out that long before that Allah had created noble human beings to accompany other human beings in managing this nature, especially from an economic point of view, they were prophets and apostles who brought the message of monotheism. One of the noblest humans ever born on this earth who brought the treatise is Muhammad Rasulullah SAW.